Evaluation of a special needs dental workshop for health professionals and students in Trinidad and Tobago - Balkaran, Ramaa; Perry, Maureen; Maharaj, Anushka; Rajhbeharrysingh, Amrita; Virtanen, Jorma I. (Frontiers in Oral Health, 2022)
Aims This study aimed to evaluate a special needs dental workshop for dentists, allied dental health professionals and students in Trinidad and Tobago. Methods This feedback study conducted in 2019–2020, included two surveys, one at the time of the workshop and a second survey one year after it. The first survey utilized an anonymous self-administered questionnaire enquiring about the reason for attendance, profession/education, demographics, and difficulties faced in treating patients with special needs. The follow-up study used an online survey tool assessing the workshop and queried comments/suggestions. The Chi-square test served for statistical analysis. Results Of the 176 attendees 131 participated (response: 74.4%). The majority (81.5%) were females. Most attendees were dental students (50.3%) or dentists (38.9%). Knowledge acquisition (73.1%) and professional development (14.2%) were the main motives for attendance while communication (31.8%) and non-compliance (34.5%) were the main problems faced in treating patients with special needs. The follow-up evaluation (post-workshop) (response: 72.5%) showed that most participants (90.5%) assessed the workshop as positive; 80% reported an increase in their knowledge and 64.2% perceived a need for further education. Conclusion These findings suggest a considerable demand for special needs dental services and continuing education and show that workshops can actively affect patient care.